2019
DOI: 10.3390/su11215901
|View full text |Cite
|
Sign up to set email alerts
|

Do the Quota Applications for Women on Boards Improve Financial Performance

Abstract: In the context of corporate governance principles, governments set regulations to increase the sustainable representation of women on boards. This paper seeks to answer the question of whether or not the application of compulsory or voluntary quotas for female board members improves firm performance. Based on difference analyses on the 2011 principles of the Capital Markets Board (CMB), we do not find significant differences between the companies with at least one female member on their board and those without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In line with previous studies conducted in contexts with a low presence of women on Boards, as in Portugal, we have not found statistically significant relationships between financial performance and the proportion of women on Boards, the Blau index, and the Shannon index [54,59,65,66]. Moreover, the presence of at least one woman on the Board does not seem to influence the financial performance of Portuguese companies, similarly to other studies [45,62,[66][67][68]. In fact, few studies, and most of them carried out in specific contexts, have documented a positive effect on financial performance for the presence of at least one woman on the Board ( [69] in banks; [15] for family firms; [70] only for ROE; [71] for SMEs).…”
Section: Regression Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies conducted in contexts with a low presence of women on Boards, as in Portugal, we have not found statistically significant relationships between financial performance and the proportion of women on Boards, the Blau index, and the Shannon index [54,59,65,66]. Moreover, the presence of at least one woman on the Board does not seem to influence the financial performance of Portuguese companies, similarly to other studies [45,62,[66][67][68]. In fact, few studies, and most of them carried out in specific contexts, have documented a positive effect on financial performance for the presence of at least one woman on the Board ( [69] in banks; [15] for family firms; [70] only for ROE; [71] for SMEs).…”
Section: Regression Analysissupporting
confidence: 90%
“…The first consisted in introducing as independent variables lagged financial performance variables (1 year lag for ROA and Tobin's Q), because managers and investors may adopt strategies based on past performance that may affect future performance [72]. In the second modification, an alternative accounting measure of financial performance was used-return on equity (ROE)-computed as the ratio of net income to equity [41,42,53,68,70]. The results, presented in Appendix B, in Tables A2 and A3, respectively, do not change the previous conclusions regarding the effect of gender diversity on financial performance.…”
Section: Robustness Testsmentioning
confidence: 99%
“…Recent meta-analyses and studies based on longitudinal data have shown a null or negative effect of female board representation on firm value (Farrell and Hersch 2005, Adams and Ferreira 2009, Carter et al 2010, Dobbin and Jung 2011, Ahern and Dittmar 2012, Matsa and Miller 2013, Pletzer et al 2015, Post and Byron 2015 (According to Solal andSnellman, 2019, p. 1270). On a sample of Turkish firms, Yıldız et al (2019) find that the ROA of Turkish companies with 25% and more female members is lower than the companies with less than 25% female members, while Bektur and Arzova (2022) show that the percentage of women in the firm's workforce harms firm performance. Concerning gender effect on CSR, or CSR disclosure, Amorelli and García-Sánchez (2021, p. 538) find that nearly 25% of studies published in the leading academic journals according to the Journal Citation Reports of the ISI Web of Knowledge from 2000 to 2020 demonstrate a non-significant or negative relationship between the presence of women and CSR performance and CSR reporting practices.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…Setting gender quotas are not enough to improve organizational performance. Women must also be given the resources, authority, knowledge, and skills to perform well (Yıldız et al, 2019).…”
Section: Gender Quotas Matter Most When Based On Competenciesmentioning
confidence: 99%